SISTEM INFORMASI WARTA JEMAAT GEREJA BATAK KARO PROTESTAN (GBKP) BERBASIS WEB - Evi Florentina Br Ginting; Mahdianta Pandia (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2020)
This Web-Based Gereja Batak Karo Protestan (GBKP) newslatter information system aims to accelerate and facilitate the congregration in obtaining congregational news information. All informatio n and data processing of the Web-based Gereja Batak Karo Protestan (GBKP) congregation is presented in a series of systems in the form of an online dynamic web and designed using the PHP programming language and the database used is MySQL. With this system, it can reduce errors in data processing, so that the information generated is faster and more accurate and services to the congregration will increase